Sustaining Control of Schistosomiasis Mansoni in Western Côte d'Ivoire: Results from a SCORE Study, One Year after Initial Praziquantel Administration. - Rufin K Assaré; Yves-Nathan; Patrick K Yao; Nicaise A N'Guessan; Mamadou Ouattara; Ahoua Yapi; Jean T Coulibaly; Aboulaye Meïté; Eveline Hürlimann; Stefanie Knopp; Jürg Utzinger; Eliézer K N'Goran (Public Library of Science (PLoS), 2016)
BACKGROUND:The Schistosomiasis Consortium for Operational Research and Evaluation (SCORE) has launched several large-scale trials to determine the best strategies for gaining and sustaining control of schistosomiasis and transitioning toward elimination. In Côte d'Ivoire, a 5-year cluster-randomized trial is being implemented in 75 schools to sustain the control of schistosomiasis mansoni. We report Schistosoma mansoni infection levels in children one year after the initial school-based treatment (SBT) with praziquantel and compare with baseline results to determine the effect of the intervention. METHODOLOGY:The baseline cross-sectional survey was conducted in late 2011/early 2012 and the first follow-up in May 2013. Three consecutive stool samples were collected from 9- to 12-year-old children in 75 schools at baseline and 50 schools at follow-up. Stool samples were subjected to duplicate Kato-Katz thick smears. Directly observed treatment (DOT) coverage of the SBT was assessed and the prevalence and intensity of S. mansoni infection compared between baseline and follow-up. PRINCIPAL FINDINGS:The S. mansoni prevalence in the 75 schools surveyed at baseline was 22.1% (95% confidence interval (CI): 19.5-24.4%). The DOT coverage was 84.2%. In the 50 schools surveyed at baseline and one year after treatment, the overall prevalence of S. mansoni infection decreased significantly from 19.7% (95% CI: 18.5-20.8%) to 12.8% (95% CI: 11.9-13.8%), while the arithmetic mean S. mansoni eggs per gram of stool (EPG) among infected children slightly increased from 92.2 EPG (95% CI: 79.2-105.3 EPG) to 109.3 EPG (95% CI: 82.7-135.9 EPG). In two of the 50 schools, the prevalence increased significantly, despite a DOT coverage of >75%. CONCLUSIONS/SIGNIFICANCE:One year after the initial SBT, the S. mansoni prevalence had decreased. Despite this positive trend, an increase was observed in some schools. Moreover, the infection intensity among S. mansoni-infected children was slightly higher at the 1-year follow-up compared to the baseline situation. Our results emphasize the heterogeneity of transmission dynamics and provide a benchmark for the future yearly follow-up surveys of this multi-year SCORE intervention study.